Evaluation of quality of life in women with overactive bladder (a survey) - F N Makhmejanova (Гинекология, 2014)
The prevalence of overactive bladder syndrome, or urinary frequency and urgency - that is an average of 17%, limited the effectiveness of treatment and a significant decrease in quality of life determine the relevance of this work.